Importance of muscle mass in acute tubular necrosis due to rhabdomyolisis: Case report [Rabdomi̇yoli̇ze baǧli geli̇şen akut tubuler nekrozda kas ki̇tlesni̇n önemi̇: Olgu sunumu] - (:unkn) unknown (My University, 2006)
A 30 year old male patient presented to our emergency clinic complaining of left upper quadrant pain. We learned he had been in a fight, assaulted with fists and iron bricks and wounded in his abdomen, thorax and right arm. Clinical examination revealed echymotic areas in his thorax, back and right arm; tenderness in the left upper quadrant of abdomen. In laboratuvary tests creatinin phosphokinase (CPK), creatinin(Cr) and potassium(K+) levels were high. The patient was admitted to emergency service with a diagnosis of rhabdomyolysis. We started izotonic saline infusion, sodium bicarbonate and furosemide treatment. His serum levels returned to normal values on the fourth day of his admission. In a trauma patient independent of extent of muscle damage if enzyme levels are high; a probability of acute tubuler necrosis risk is also high. In patients presented to emergency clinic due to trauma, without looking at the extent of muscle injury; CPK, Cr, K levels must be checked, and if they are high, to prevent complications treatment must be started immediately to prevent complications.
Keywords: Acute tubuler necrosis; Muscle damage extent; Rhabdomyolysis